2014
DOI: 10.1038/ja.2014.123
|View full text |Cite
|
Sign up to set email alerts
|

Novonestmycins A and B, two new 32-membered bioactive macrolides from Streptomyces phytohabitans HBERC-20821

Abstract: Two new 32-membered macrolide compounds, named Novonestmycins A (1) and B (2), were isolated from the soil strain Streptomyces phytohabitans HBERC-20821. Their structures were elucidated by using spectroscopic methods, including 1D, 2D-NMR and MS spectrometry. The two compounds showed strong activities against the phytophathogenic fungi Corynespora cassiicola, Rhizoctonia solani and Septoria nodorum, with MIC values of 0.78, 0.39 and 0.78 μg ml(-1), respectively. In addition, the two compounds exhibited potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
(4 reference statements)
2
15
0
Order By: Relevance
“…Furthermore, the UV–Vis spectrum associated with these compounds was suggestive of a tetraene moiety in each, due to the typical absorption band from 280 to 340 nm with a clear maxima at 312 nm (Supplementary material). Taken together, these data suggest the presence of tetraene polyols in the extract, which would be in-line with the production of PKS or hybrid PKS natural products by similar actinomycetes such as the novonestmycins, separacenes, bahamaolides and marinisporolides (Kwon et al 2009; Kim et al 2012; Bae et al 2013; Wan et al 2015). However, the parent masses observed in this study were not found to correlate with any known molecules of this class in the MarinLit or Dictionary of Natural Products databases.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, the UV–Vis spectrum associated with these compounds was suggestive of a tetraene moiety in each, due to the typical absorption band from 280 to 340 nm with a clear maxima at 312 nm (Supplementary material). Taken together, these data suggest the presence of tetraene polyols in the extract, which would be in-line with the production of PKS or hybrid PKS natural products by similar actinomycetes such as the novonestmycins, separacenes, bahamaolides and marinisporolides (Kwon et al 2009; Kim et al 2012; Bae et al 2013; Wan et al 2015). However, the parent masses observed in this study were not found to correlate with any known molecules of this class in the MarinLit or Dictionary of Natural Products databases.…”
Section: Discussionsupporting
confidence: 56%
“…Since there was no change in the total number of carbon and protons in 2 as compared to 1, the observed 80 mass unit loss in HRMS data indicated the presence of a hydroxyl group instead of the sulfate group at C-17. This was further supported by the observed 8.2 ppm upfield shift for C-17 in 2 (2: δ C 70.0; 1: δ C 78.2) [36] and HMBC correlation from H-16 to C-17 (Additional file 1: Figures S1, S11). As in 1, the presence of malonate ester group was evidenced by the methylene singlet at δ H 2.91, δ C 45.9 in DMSO-d 6 NMR data.…”
Section: Isolation and Identification Of Notonesomycins A (1) And A Nsupporting
confidence: 56%
“…1. The relative configurations at most stereogenic centers were determined by comparison with the 13 C NMR data of novonestmycins A and B [36] and brasilinolides A and C [33] except for those at C-5, -7, -12, -13, and -14, which remain unassigned. The relative configurations of 1 were assumed to be the same as 2 based on high similarity of their NMR data ( Fig.…”
Section: Isolation and Identification Of Notonesomycins A (1) And A Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Many novel antibiotics such as bafilomycin K produced by Streptomyces flavotricini Y12-26 (Zhang et al, 2011), elaiomycins B produced by Streptomyces sp. BK190 (Kim et al, 2011) and novonestmycins produced by S. phytohabitans (Wan et al, 2015) are being evaluated as new biofungicides.…”
Section: Introductionmentioning
confidence: 99%